STRATEGI MAHASISWA PROGRAM STUDI PENDIDIKAN GURU MADRASAH IBTIDAIYAH IAI AL-AZIS DALAM PENYELESAIAN TUGAS AKHIR TEPAT WAKTU - Chasan Arif; humaeroh, iis; Dede Indra Setiabudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the strategies employed by students of the Primary School Teacher Education Program (PGMI) at IAI Al-AZIS to complete their undergraduate thesis on time, as well as to identify the challenges they face. The research employed a qualitative approach with a descriptive method. Data were collected through semi-structured interviews, observation, and documentation, and analyzed using Miles & Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The findings revealed that students’ success in completing their thesis on time was determined by effective time management, strong intrinsic motivation, intensive communication with academic supervisors, and institutional support. The obstacles encountered include internal factors such as laziness, procrastination, and limited academic writing skills, as well as external factors such as limited references, overloaded supervisor schedules, and economic constraints. To overcome these barriers, students applied adaptive strategies such as creating a writing timeline, utilizing peer study groups, and employing digital applications (Mendeley, Google Scholar) to accelerate the writing process. This study concludes that timely thesis completion is the result of a synergy between internal, external, and spiritual factors, and contributes to strengthening the concept of self-regulated learning while providing practical recommendations for students and higher education institutions. Keywords: Student Strategies, Timely Thesis Completion, Time Management, Learning Motivation, Self-Regulated Learning;